Occurrence and Severity of Catheter-Related Bladder Discomfort of General Anesthesia Plus Epidural Anesthesia vs. General Anesthesia in Abdominal Operation With Urinary Catheterization: A Randomized, Controlled Study - Sun, Shunxiang; Wang, Cheng; Zhang, Jun; Sun, Pengfei (Frontiers in Surgery, 2021)
Background: This randomized, controlled study aimed to investigate the effect of general anesthesia plus epidural anesthesia on catheter-related bladder discomfort (CRBD) in patients who underwent abdominal operation with urinary catheterization. Methods: A total of 150 patients scheduled for abdominal operation under anesthesia with urinary catheterization were randomized to receive general anesthesia plus epidural anesthesia (N=74, GA+EA group) or general anesthesia (N=76, GA group). The occurrence and severity of CRBD, systolic blood pressure (SBP), diastolic blood pressure (DBP), and heart rate (HR) were recorded at 0 hour (h), 0.5h, 1h and 3h after tracheal extubation. Besides, postoperative adverse events were assessed. Results: The occurrence and severity of CRBD at 0h, 0.5h, 1h and 3h were all reduced in GA+EA group compared to GA group (all P<0.05). Meanwhile, subgroup analyses showed that the reduction of occurrence and severity of CRBD in GA+EA group compared to GA group was more obvious in male patients and patients ≥50 years. Besides, SBP at 0h, 0.5h, 1h and 3h, as well as DBP at 0h, 0.5h and 3h were all decreased in GA+EA group compared to GA group (all P<0.05), while HR was increased at 0h in GA+EA group compared to GA group (P=0.034). Moreover, the occurrence of pain, severity of pain and occurrence of vomiting were similar between GA+EA group and GA group (all P>0.05). Conclusion: General anesthesia plus epidural anesthesia decreases CRBD occurrence and severity with tolerable safety compared with general anesthesia in patients who undergo abdominal operation with urinary catheterization.